Climate Risk Management for Sustainable Landscape Development in Ethiopia: Training Manual Development for Extension Officers on Integrated Land Management in Ethiopia - Belay, Berhanu; Ambaw, Gebermedihin; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Climate change has emerged as a major driver of land degradation, intensifying climate-related hazards such as flash floods, droughts, and soil erosion. In response to the urgent need for climate education and sustainable land management, a customized Facilitators’ Guide and Reference Manual titled Climate Risk Management in Integrated Land Management and Development (CRMILMD) was developed. Adapted from the "Climate Risk Management in Agricultural Extension" manual by IRI and AICCRA, the CRMILMD resource was co-created through a collaborative write-up workshop involving 13 universities, AICCRA, and GIZ staff, under a Training of Trainers (ToT) framework. The write-up workshop was conducted on September 1-5, 2025. The manual aims to enhance the capacity of extension officers, community leaders, and farming communities to manage climate risks and adopt sustainable land restoration practices. It is projected that by 2025, approximately 303 extension officers and 20,000–30,000 community leaders and farmers will be trained using this resource. The training outcomes are intended to be integrated into local governance structures at both the woreda and kebele levels, with ongoing support and monitoring provided by extension staff. Designed for long-term application, the CRMILMD manual contributes to building climate resilience and promoting sustainable land management on a large scale.